Implementasi Energi Surya sebagai Sumber Energi Listrik pada Kantin Sehat Kelompok Tani (PokTan) Mustika Kramat Jati, Jakarta Timur - Antonius Doddy Tyas Prasetyo; Eva Magdalena Silalahi Silalahi; Judo Ignatius Nempung; Tahan Lumban Tobing Tobing (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2026)
Solar Energy can be utilized as an alternative electrical energy source for communities to reduce routine expenditures, particularly in micro-business sectors like food stalls or canteens. This Community Service (PkM) project aims to implement a Solar Power Plant (PLTS) to supply the electrical load of the Kantin Sehat Kelompok Tani (PokTan) Mustika in Kramat Jati, East Jakarta, and to analyze its economic impact on monthly electricity bills. The implementation method consists of four main stages: energy auditing of the canteen's electrical load, system capacity designing (sizing), installation of main components (10 units of 100 Wp solar panels and a 2 kVA zero-export inverter), and operational as well as financial evaluation. The results indicate that the installed PLTS system operates effectively in meeting the canteen's daily power demands. This implementation successfully reduces reliance on the national grid (PLN) during daytime, yields operational cost efficiency for the managers of Kantin Sehat PokTan Mustika, and enhances the partner's understanding regarding the independent maintenance of renewable energy systems.